THE SIGNIFICANCE OF STRESS AFFECTING SOLDIERS PARTICIPATING IN INTERNATIONAL MISSIONS - Giebułtowska Magdalena (2021)
The objective of the present article is to determine the negative changes that stress experienced by soldiers of participants in international missions may trigger in their functioning. It is assumed that these changes can be so extensive and intense that they will be able to limit the ability of soldiers to take action. Therefore, their participation in the international mission may be limited. This objective can be achieved by using methods of analysis and criticism of subject literature, as well as by induction and deduction. In the result of the carried analysis the author comes to the conclusion that stress can negatively affect the physical and psychological functioning of soldiers participating in international missions. Mission stressors can occur on the physical, cognitive, emotional, social and spiritual levels. They can trigger negative changes that are noticeable in the behaviour of soldiers. Furthermore they can also be so extensive that they can affect their ability to take combat action. The quoted research results are significant, as the description of how exactly the stress-induced negative changes in a single soldier can affect not only the safety of that individual, but also others, and thus the success of the entire mission.